Obtaining commercial humic products from uncomposted manures: previous acid hydrolysis to enhance yields - Carla Bellera; Issa Abaalkheel; Pere Rovira; Jamal Alrefai (International Journal of Recycling of Organic Waste in Agriculture)
Purpose In Saudi Arabia, owing to the abundant livestock, manures are a source of commercial humic amendments. Climate (hot weather plus scarcity of water sources) makes composting very difficult and compulsory to obtain these humic amendments without any previous composting step. A substantial fraction of manures, cellulosic in nature, are unextractable by alkaline solutions. Our aim is to verify whether a sequential combination of acid hydrolysis and KOH extraction could result in higher yields and better quality of the humic extract. Methods Acid hydrolysis was applied to manures either (1) in a single step, with HCl or H2SO4, or (2) in two steps (Saeman method). In both cases, acid hydrolysis was followed by extraction with hot KOH. Results Acid hydrolysis before KOH extraction increases total extracted organic matter. If acid hydrolysis is performed, the proportion of humic fractions in the KOH extract alone is strongly increased, reaching very high values (up to 80 % of C in the KOH extract after Saeman acid hydrolysis). Acid hydrolysis enhances some optical indicators of humification (E4E6, aromaticity, EBTZ ratio) in the KOH extract. Nevertheless, because increasing acid concentration enhances carbohydrate extraction but decreases that of compounds other than carbohydrates, the overall result may be a drop in the proportion of humic fractions in the whole extracted matter (acid hydrolysate ? KOH extract). Conclusions Acid hydrolysis improves yields of commercial humic extracts from manures. However, care must be taken to avoid a decrease in the richness of humic fractions in the obtained products.